2010
DOI: 10.1007/s11661-010-0333-0
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Resistance Spot Welding of Magnesium to Steel

Abstract: A novel technology has been developed for the resistance spot welding (RSW) of magnesium to steel producing joint strength as high as 95 pct of that of Mg to a Mg joint. The mechanisms of the dissimilar joining have been investigated using mechanical testing and metallurgical examination employing scanning electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray diffraction. The results show that the mechanisms of joining during RSW of a magnesium alloy to Zn-coated steel involve braze welding, sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…Several papers have been published to identify the effect of G and R on the microstructure in the FZ. [31][32][33][34][35][36] To facilitate a better understanding of the effect of G/R and G 9 R on the morphology and size of solidification microstructures, a schematic plot is shown in Figure 5. [37] It is observed that the moderate temperature gradient at the boundary of fusion line resulted in columnar dendrites in both welded joints, whereas in the center of the FZ, dendrites became equiaxed because of a lower temperature gradient.…”
Section: A Microstructurementioning
confidence: 99%
“…Several papers have been published to identify the effect of G and R on the microstructure in the FZ. [31][32][33][34][35][36] To facilitate a better understanding of the effect of G/R and G 9 R on the morphology and size of solidification microstructures, a schematic plot is shown in Figure 5. [37] It is observed that the moderate temperature gradient at the boundary of fusion line resulted in columnar dendrites in both welded joints, whereas in the center of the FZ, dendrites became equiaxed because of a lower temperature gradient.…”
Section: A Microstructurementioning
confidence: 99%
“…Results show the good joining strength can be obtained, which reaches 70-80 % of the Mg substrate. Resistance spot welding (RSW) of AZ31B Mg alloy to Zn-coated steel also produced the joint strength as high as 95 % of that of Mg-Mg joint [10]. However, *Corresponding author: tel.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the very large differences in the physical properties of Mg and steel, and poor interactions, conventional processes have exhibited some disadvantages, such as a large heat-affected zone (HAZ), solidification cracking, porosity, evaporative loss of the alloying elements, and high residual stresses resulting in low welding joint strength [12,13]. After consulting a large volume of literature, the lap joints of Mg-steel obtained by fusion welding methods have maximum shear loads of 5 kN [14] (resistance spot welding) and the minimum value of 767 N (laser welding-brazing) [15].…”
Section: Introductionmentioning
confidence: 99%